Leaf trait variation across Mediterranean forest endemics: drivers and evidence for lower resource acquisition ability than in widespread forest congeners - Selvi, Federico; Carrari, Elisa; Campetella, Giandiego; Canullo, Roberto; Chelli, Stefano; Coppi, Andrea; Farris, Emmanuele; Maccioni, Alfredo; Mascia, Francesco; Postiglione, Nicola; Rosati, Leonardo; Santi, Ilaria; et al. (Frontiers in Plant Science, 2025)
IntroductionDespite their biogeographical relevance, the trait space exploited by endemic plants of Mediterranean forests remains largely unknown. Understanding their functional divergence from widespread congeners is key to explaining their restricted distribution, ecology, and resource-use strategies.MethodsHere, we analyzed interspecific variability in leaf economic traits capturing plant strategies of resource-use such as leaf area (LA), specific leaf area (SLA), leaf mass per area (LMA), leaf dry matter content (LDMC), leaf nitrogen content per unit dry mass (Nmass) and carbon to nitrogen ratio (C:N ratio), across 45 endemic taxa of Mediterranean forests. The influence of environmental variables and the phylogenetic signal of traits were examined to identify the main drivers. Next, we performed paired comparisons in 27 endemic-non endemic pairs, with allopatric, parapatric and sympatric distribution.Results and discussionOverall, trait variability within endemics was remarkably ample, reflecting their diversity in functional types, phylogenetic relationships and biogeographical contexts. Endemics were widely distributed along the resource use gradient associated with LA, LMA and Nmass. Herbaceous taxa showed more resource-acquisitive trait values and prevalence of C and R strategies, while woody endemics were more resource-conservative and stress-tolerant. Traits showed a phylogenetic signal of variable intensity depending on the metrics, with Pagel’s λ approaching the Brownian model for LA and LMA. Environmental factors variously influenced trait variation. LA decreased with temperature and depended on forest type, while LDMC decreased with latitude and precipitation. LMA increased with temperature and varied with ecoregion and forest type, while Nmass decreased with latitude and increased with precipitation. Species pairs analysis revealed a negative effect of the endemic condition on LA, but positive on LMA. Compared with widespread congeners, this pointed to a lower acquisitive ability and stronger resource conservation attitude, also confirmed by CSR strategies. Differences in LA and LMA within allopatric and parapatric pairs were larger than in sympatric pairs, suggesting the role of vicariance in key leaf trait divergence. In advancing our understanding of the functional and ecological characteristics of Mediterranean endemic forest plants, this study may help to predict the effects of the increasing pressures to their habitat and support strategies for their conservation.